ANALYSIS OF THE CONTRIBUTION OF ISLAMIC CIVILIZATION TO WESTERN DEVELOPMENT: SOCIO-POLITICAL IMPLICATIONS - Naimah, Elok Nadiatun; Mujab, M (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2025)
Abstract: This study examines the contribution of Islamic civilization to the development of the West, especially the socio-political impact that is often overlooked. Its main objective was to identify the transfer of knowledge and its influence on the socio-political structure of Europe from the Middle Ages to the Renaissance. The method uses a systematic literary study and historical analysis of the work of Al-Mawardi ( Al-Ahkam al-Sultaniyyah ), Ibn Rushd, as well as cultural interactions in Al-Andalus and Sicily. The results show a dual contribution: epistemological through Ibn Rushd's preservation of Aristotle which became the basis of European scholasticism, and transformational through Al-Mawardi's model of government which introduced justice, moral legitimacy, and early checks and balances. The Islamic Trade Network and the city of Cordoba sparked the emergence of Europe's first university and pluralistic civil society.These contributions form the foundation of modern Western inclusive democracy, demanding a reinterpretation of anti-Eurocentric history. Islamic Civilization proved to be an essential catalyst of Western modernity. Keywords: Islamic Civilization; Socio-Political Implications; Knowledge Transfer;